The Walsh Family Resilience Questionnaire: Validity evidence from Portugal - Morais, I.; Carneiro, F. A.; Sinval, J.; Costa, P. A.; Leal, I. (Family Relations, 2024)
Background Family resilience refers to a family's capacity to face and manage adversities, emerging as a stronger and more resourceful unit. A family system approach enlarges the lens to the broad relational network, identifying potential resources for resilience within the immediate and extended family. This approach emphasizes a family's innate ability to adapt in the face of adversities. Objective This study aims to test the psychometric properties of the Walsh Family Resilience Questionnaire (WFRQ) using a sample of Portuguese caregivers with children aged between 10 and 15 years. Method A total of 267 caregivers of children aged 10 to 15 years completed a sociodemographic questionnaire and the WFRQ. Analyses were performed to evaluate the WFRQ's validity evidence based on the internal structure (i.e., dimensionality and reliability) and on its relationship to other variables. Results The findings supported a 31-item version of the WFRQ with one third-order latent factor, three second-order factors, and nine first-order factors for the Portuguese population. The WFRQ exhibited satisfactory validity evidence based on the internal structure and relation to other variables. Conclusion Overall, the results of this study demonstrate the suitability of the WFRQ as a holistic measure to gauge resilience at the family level, going beyond individual assessments. Implications This instrument holds significant utility in family resilience research and clinical interventions involving families.